Pendidikan Spiritual Dalam Tradisi Istighosah Santri Pondok Pesantren Al Mahrusiyah III Ngampel - Fuad Hasim; Yasin Nurfalah (eL Bidayah: Journal of Islamic Elementary Education, 2020)
This research was conducted to determine how spiritual education is in the istighotsah tradition of HM Al-Mahrusiyah III Ngampel Islamic boarding schools. Spiritual education is education that instills a sense of love for Allah in a person's heart which makes him expect Allah's blessing, both in every word, deed, attitude and behavior. Itighotsah is an expectation of help from Allah, because Allah is the most helper of everything and only Allah who grants all kinds of human needs that become their wants and needs. In this study, the authors used a descriptive qualitative approach which moved from two questions, namely; 1) How is the process of Istighotsah activity 2) How is the spiritual change felt after attending Istighotsah. With the questions that formulated the problem, the researcher obtained the following results: 1) The pre-istighotsah stage, carried out for operation. The istighotsah stage, there are three parts in it, the first is Muqodimah, namely the Tasbih, Witir and Hajat circumcision prayers. Second Contents, namely tawashul, tahlil and reciting dhikr. Third Closing, read Hisbus Salamah, Hisbun Nasar and prayer istighotsah. Post istighotsah stage. Carry out the subuh prayer in congregation. 2) calms the soul, because in it there are things that bring calm, such as circumcision prayer, dzikrullah in reciting tahlil, tahmit, tasbih, takbir and sholawat. [Penelitian ini dilakukan untuk mengetahui bagaimana pendidikan spiritual dalam tradisi istighotsah santri Pondok Pesantren HM Al-Mahrusiyah III Ngampel. Pendidikan spiritual merupakan pendidikan yang menanamkan rasa cinta kepada Alloh di dalam hati seseorang yang menjadikannya mengharap ridho Alloh, baik di setiap ucapan, perbuatan, sikap dan tingkah laku. Itighotsah merupakan pengharapan adanya pertolongan dari Alloh, karena Alloh lah yang maha penolong segalanya dan hanya Alloh yang maha mengabulkan atas segala macam kebutuhan manusia yang menjadi keinginan serta kebutuhannya. Pada penelitian ini penulis menggunakan pendekatan kualitatif diskriptif yang beranjak ari dua pertanyaan, yaitu ; 1) Bagaimana Proses Kegiatan Istighotsah 2) Bagaimana Perubahan Spiritual yang Dirasakan Setelah Mengikuti Istighotsah. Dengan adanya pertanyaan yang menjadi rumusan masalah tersebut, peneliti memperoleh hasil sebagai berikut: 1) Tahap pra istighotsah, dilakukan pengoprakan. Tahap istighotsah, ada tiga bagian didalamnya, pertama Muqodimah, yaitu sholat sunat Tasbih, Witir dan Hajat. Kedua Isi, yaitu tawashul, tahlil dan membaca dzikir. Ketiga Penutup, membaca Hisbus Salamah, Hisbun Nasar dan do’a istighotsah. Tahapan pasca istighotsah. Melaksanakan sholat subuh berjama’ah. 2) menenangkan jiwa, karena di dalamnya terdapat hal-hal yang mendatangkan ketenangan, seperti sholat sunat, dzikrullah dalam pembacaan tahlil, tahmit, tasbih, takbir dan sholawat]